Local Government Policies for Empowering Heritage Tourism in Surabaya’s Old City - Wicaksono, Lintang Permata; Kamariyah, Sri; Dwijosusilo, Kristyan; Mustofa, Amirul (Socious Journal, 2025)
Surabaya's Old City is a heritage area with significant potential as a historical tourism destination. However, its management and the empowerment of local communities continue to face various challenges, including the dominance of top-down policies, limited community involvement, and weak digital branding strategies. This study aims to evaluate the effectiveness of Surabaya’s local government policies in supporting heritage tourism empowerment by applying the Community-Based Tourism (CBT) approach and the Pentahelix model. The research employs a qualitative method using semi-structured interviews, participatory observation, and document analysis. The findings indicate that community participation remains symbolic, the empowerment of MSMEs is suboptimal, and collaboration among Pentahelix actors lacks synergy. Moreover, the digital promotion strategy for the heritage area is considered insufficiently innovative. This study recommends a reformulation of more participatory policies, strengthening the role of MSMEs, and optimizing digital branding to support the sustainable development of Surabaya's heritage tourism.